2017
DOI: 10.26719/2017.23.7.461
|View full text |Cite
|
Sign up to set email alerts
|

Patients' attitudes and preceptions regrding research and their rights: a pilot survey study from the Middle East

Abstract: Attitudes et perceptions des patients à l'égard de la recherche et de leurs droits : étude pilote au Moyen-Orient RESUME La surveillance éthique et réglementaire de la recherche peut ne pas être optimale dans les pays à revenu faible et intermédiaire. Afin de déterminer les attitudes et les perceptions des patients à l'égard de la participation à la recherche et des perceptions de leurs droits, nous avons recruté 202 participants dans des hôpitaux en Arabie saoudite, en Égypte, au Liban et au Soudan, et leur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…[11,16,24] They were mainly resistant to participating in drug trials, including invasive procedures such as tissue biopsy. [11,14,23,24,31,32] This was opposed by study findings that reported a high proportion of patients considered participation in trials involving repeat biopsies. However, the study included patients with gastrointestinal malignancies or lymphoma only, and their views on biopsies may differ from other patients.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…[11,16,24] They were mainly resistant to participating in drug trials, including invasive procedures such as tissue biopsy. [11,14,23,24,31,32] This was opposed by study findings that reported a high proportion of patients considered participation in trials involving repeat biopsies. However, the study included patients with gastrointestinal malignancies or lymphoma only, and their views on biopsies may differ from other patients.…”
Section: Discussionmentioning
confidence: 94%
“…This might come in the shape of accessing hospital care or costly drugs that are more effective than the available treatments, drugs of fewer side effects or otherwise unavailable, as well as receiving better treatment or more attention from healthcare providers. [ 15 , 17 , 21 23 , 27 , 28 , 31 , 33 ] In addition to that, participation was motivated by having financial gains, expressing their opinions, sharing their complaints, or getting to learn about the scientific topic being researched. [ 14 , 20 , 21 , 23 , 25 , 28 , 30 , 31 , 33 ] Moreover, few of these studies showed that patients are often motivated to participate in research if they knew in advance that they would have access or receive feedback on their test results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations